ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Jasa Sektor Transportasi di Bursa Efek Indonesia Periode 2013-2017) - Prayogo, 15.05.52.0263; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study examines the effect of investment opportunity set, asset structure, debt structure, profitability, firm size and firm age on firm value. This research was conducted on the Indonesia Stock Exchange using the analysis unit of the transportation sector service company. The sampling method uses purposive sampling with a sample of 114 companies with a research period of 2013 - 2017. The relationship and / or influence between variables is explained using the multiple regression analysis method. The results of the study indicate that the investment opportunity set, profitability, debt structure, company size and age of the company have no significant effect on firm value. The the asset structure have a significant negative effect on firm value.